Cancer Pain Control for Advanced Cancer Patients by Using Autonomic Nerve Pharmacopuncture - Hwi-joong Kang; Jung-won Yoon; Ji-hye Park; Chong-kwan Cho; Hwa-seung Yoo (Korean Pharmacopuncture Institute, 2014)
Objectives: The purpose of this study is to report a case series of advanced cancer patients whose cancer pain was relieved by using autonomic nerve pharmacopuncture (ANP) treatment. ANP is a subcutaneous injection therapy of mountain ginseng pharmacopuncture (MGP) along the acupoints on the spine (Hua-Tuo-Jia-Ji-Xue; 0.5 cun lateral to the lower border of the spinous processes of vertebrae) to enhance the immune system and to balance autonomic nerve function. Methods: Patients with three different types of cancer (gastric cancer, lung cancer, colon cancer with distant metastases) with cancer pain were treated with ANP. 1 mL of MGP was injected into the bilateral Hua-Tuo-Jia-Ji-Xue on the T1-L5 sites (total 12 ─ 20 mL injection) of each patient's dorsum by using the principle of symptom differentiation. During ANP treatment, the visual analogue scale (VAS) for pain was used to assess their levels of cancer pain; also, the dosage and the frequency of analgesic use were measured. Results: The cancer pain levels of all three patients improved with treatment using ANP. The VAS scores of the three patients decreased as the treatment progressed. The dosage and the frequency of analgesics also gradually decreased during the treatment period. Significantly, no related adverse events were found. Conclusion: ANP has shown benefit in controlling cancer pain for the three different types of cancer investigated in this study and in reducing the dosage and the frequency of analgesics. ANP is expected to be beneficial for reducing cancer pain and, thus, to be a promising new treatment for cancer pain.